Ecological and economic management of innovation activity of enterprises - Dankevych, Andrii; Sosnovska, O.; Dobrianska, Natalia; Mazur, Yuriy; Ingram, Keisha Laraine (My University, 2021)
To analyze the current state of innovation and environmental projects, to develop management strategies and algorithms for project environmental and economic management in subsoil use, to propose a mathematical model of the system of perception and support of solutions for effective environmental and economic management

Проаналізувати сучасний стан інноваційно-екологічних проектів, розробити стратегію управління та алгоритми проектного еколого-економічного управління надрокористуванням, запропонувати математичну модель системи сприйняття та підтримка рішень для ефективного еколого-економічного управління
Keywords: innovation (ecology); economic efficiency; environmental and economic management; mining enterprises; інновації (екологія); економічна ефективність; еколого-економічний менеджмент; гірничі підприємства; кафедра економіки і права